Amalan sumber manusia dan keseimbangan tuntutan kerja-tanggungjawab peribadi terhadap kepuasan kerja: kajian di Jabatan Keselamatan Universiti Utara Malaysia - Muhammad Hafiz, Mohd Ghazali (2016)
Job satisfaction very important role in producing quality workforce. The objective this study is to examine the relationship between HR practices and demand balance and job satisfaction. This study applied questionnaires and had involved 104 staffs from Security of Departments, Universiti Utara Malaysia. The results of this study show that human resource practices were not significantly related to job satisfaction. The demographics factor of age and length of service also showed no difference in relation to job satisfaction and demands personal responsibility, but the gender factor has a significant difference. Accordingly, for the performance of the training program or human resource management which demographic characteristics are taken into consideration for program content development.